Strengthening capacity for resilient food systems: Approaches and research gaps - Babu, Suresh Chandra; Blom, Sylvia (International Food Policy Research Institute, 2014)
In the wake of the food and financial crises of 2007–2008 and 2011, building resilient food systems to achieve food security for all has become one of the top goals of the development agenda.